2020
DOI: 10.1038/s41598-020-70603-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the deterioration of periventricular–intraventricular hemorrhage in preterm infants

Abstract: Preterm infants with periventricular-intraventricular hemorrhage (PV-IVH) have a high risk of neurological sequelae, with severity depending on the severity of the PV-IVH. Previous studies on the pathogenesis of PV-IVH have focused mainly on comparisons of perinatal risk factors between patients with and without PV-IVH. Notably, most cases of PV-IVH occur within the first 3 days after birth, and the condition may worsen within 1 week following the initial diagnosis. However, the risk factors that contribute to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 36 publications
(39 reference statements)
5
24
0
5
Order By: Relevance
“…This study adopted the Papile's grading system [18,19] where Grade I represented subependymal haemorrhage, Grade II -intraventricular haemorrhage without dilation, Grade III -intraventricular haemorrhage with ventricular dilation and Grade IV -intraventricular haemorrhage with parenchymal haemorrhage; the most prevalent grade was Grade I at 51.4% with equal proportions for Grades II, III and IV at 16.2% each. This grade I finding, although lower than that reported in a study conducted in China [4] at 63.2%, shows a similar trend in the highest proportion by IVH grade. However, there were contrasting findings in Grade II and III/IV at 12.3% and 24.1% respectively, a difference that could be attributed to the retrospective design of the study compared to the current study which adopted a prospective study design.…”
Section: Table 4: Factors Associated With Neonatal Mortality In Ivh D...supporting
confidence: 66%
See 1 more Smart Citation
“…This study adopted the Papile's grading system [18,19] where Grade I represented subependymal haemorrhage, Grade II -intraventricular haemorrhage without dilation, Grade III -intraventricular haemorrhage with ventricular dilation and Grade IV -intraventricular haemorrhage with parenchymal haemorrhage; the most prevalent grade was Grade I at 51.4% with equal proportions for Grades II, III and IV at 16.2% each. This grade I finding, although lower than that reported in a study conducted in China [4] at 63.2%, shows a similar trend in the highest proportion by IVH grade. However, there were contrasting findings in Grade II and III/IV at 12.3% and 24.1% respectively, a difference that could be attributed to the retrospective design of the study compared to the current study which adopted a prospective study design.…”
Section: Table 4: Factors Associated With Neonatal Mortality In Ivh D...supporting
confidence: 66%
“…This condition is multifactorial in nature and is often reported in cases of fibronectin deficiency in the germinal matrix basal lamina [3]. Intraventricular haemorrhage pathogenesis is associated with irregularities in cerebral blood flow, coagulation and platelet abnormalities that worsen the bleeding making this very critical infant in the integrity of the germinal matrix [4,5]. Some of the etiological risk factors for IVH include very low birthweight (<1500 grammes), very low to extremely low gestational age (< 32 weeks), absence of prenatal corticosteroid use for women at risk of premature mature delivery [2] and early clamping of the umbilical cord [6].…”
Section: Introductionmentioning
confidence: 99%
“…Antenatal infection, including lower genital tract infection during pregnancy, is associated with a higher risk of having severe GMH-IVH as resulted in our study. In other studies, they found that antenatal infection and maternal lower genital tract infection are risk factors for developing and early deterioration of GMH-IVH [10,5]. The study mentioned that infections and inflammatory responses are strongly associated with neonatal brain injury, including GMH-IVH.…”
Section: Table 1 Analysis Of Gestational Age In Weeks Of Mild Gmh-ivh and Severe Gmh-ivh [T-test] Grade I And Ii Grade Iii And Iv P-valuementioning
confidence: 91%
“…Early management of lower genital tract infection is essential in preventing GMH-IVH in neonates [5].…”
Section: Table 1 Analysis Of Gestational Age In Weeks Of Mild Gmh-ivh and Severe Gmh-ivh [T-test] Grade I And Ii Grade Iii And Iv P-valuementioning
confidence: 99%
See 1 more Smart Citation